Caracterização fisico-química dos blocos cerâmicos e sua influência no controle de qualidade pós queima: estudo de caso da olaria de São Francisco do Oeste/RN - Bezerra, Francisco Túlio Cezar Gonçalves (Universidade Federal Rural do Semi-Árido, 2017)
The ceramic block is one of the main products of the red ceramic most used in the various areas of civil engineering construction. The quality of its structure is linked to chemical, physical, mechanical and thermal parameters. This work aims to analyze the quality control after the burning process on the ceramic blocks of a factory located in the city of São Francisco do Oeste in the state of Rio Grande do Norte/Brazil. In order to do that, initially, an on-site inspection was performed to verify the production process, more precisely during and after the burning stage, as well as to diagnose the greatest damages caused to the brick structure. In the second phase, several physical, mechanical and geometric analyzes were carried out with the intention of verifying the conformity of the ceramic blocks required by the ABNT NBR 15270 standard, with the purpose of confirming the conformity or not of the samples under study. The technological examines performed on the samples were: linear retraction, water absorption, density and compressive strength. Although there was no control throughout the burning process, the results showed that after all the analyzes performed and comparing to the conformity of the standard, only the length (C) did not met the requirements. In a third period, the chemical characterization of the block structure was carried out by X-ray fluorescence - FRX, with the aim of obtaining the contents of the constituent elements in the raw material, and it was determined by X-ray diffraction analysis - XRD mineralogical compositions of clay. This characterization was important to determine the chemical elements that influence the defects of the blocks. The results of this structural characterization also showed that aluminum excelled in the mineralogical composition, being present in almost all the crystalline phases perceived. This is vital to understand the structural behavior of the blocks along the production line.
Keywords: Cerâmica vermelha; Conformidade; Pós queima; Red ceramics; Conformity; Post burning; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA